(untitled) (Jurnal Simki Economic, 2025)
This research aims to determine the influence of size population, unemployment, and government expenditures on poverty levels in Mimika Regency in 2011-2023. The data used in this research uses secondary data sourced from the Mimika Regency Central Statistics Agency and the Directorate General of Financial Balance, Ministry of Finance. This research uses a multiple linear regression analysis method using the OLS (Ordinary Least Square) model. Data processing uses Eviews 10 statistical testing. The results of this study show that size population has a partial positive and insignificant effect on poverty levels. Unemployment has a positive and insignificant effect on poverty levels, and government expenditures have a negative effect on poverty levels. The results of simultaneous statistical tests show that population, unemployment, and government expenditures did not have a significant effect on poverty level in Mimika Regency in 2011-2023.